2020
DOI: 10.1200/jco.19.01265
|View full text |Cite
|
Sign up to set email alerts
|

Activity of Vincristine and Irinotecan in Diffuse Anaplastic Wilms Tumor and Therapy Outcomes of Stage II to IV Disease: Results of the Children’s Oncology Group AREN0321 Study

Abstract: PURPOSE AREN0321 evaluated the activity of vincristine and irinotecan (VI) in patients with newly diagnosed diffuse anaplastic Wilms tumor (DAWT) and whether a regimen containing carboplatin (regimen UH1) in addition to regimen I agents used in the National Wilms Tumor Study 5 (NWTS-5; vincristine, doxorubicin, cyclophosphamide, and etoposide plus radiotherapy) would improve patient outcomes. PATIENTS AND METHODS Patients with stage II to IV DAWT without measurable disease received regimen UH1. Patients with s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
71
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 65 publications
(73 citation statements)
references
References 20 publications
2
71
0
Order By: Relevance
“…The NWTS-5 study did not observe an increased relapse rate among stage IV FHWT, compared to localized FHWT, stratified by 1q gain [29]. However, inferior EFS was observed in case of stage IV anaplastic histology WT (AHWT) (Table 2) [43][44][45]. AIEOP TW2003 and UKW3 reported similar findings: EFS was not different between stage I and stage IV patients when adjusted for tumor histology [5,25] (Table 3).…”
Section: Stage IVmentioning
confidence: 75%
“…The NWTS-5 study did not observe an increased relapse rate among stage IV FHWT, compared to localized FHWT, stratified by 1q gain [29]. However, inferior EFS was observed in case of stage IV anaplastic histology WT (AHWT) (Table 2) [43][44][45]. AIEOP TW2003 and UKW3 reported similar findings: EFS was not different between stage I and stage IV patients when adjusted for tumor histology [5,25] (Table 3).…”
Section: Stage IVmentioning
confidence: 75%
“…Studies have revealed that doxorubicin-induced heart failure (HF) occurs in 3%–5% of patients treated with 400 mg/m 2 doxorubicin ( 28 ). Cumulative doses of doxorubicin in patients with WT in COG and SIOP studies were no greater than 250 mg/m 2 ( 22 , 29 ). Doxorubicin hydrochloride liposomes are a novel formulation of doxorubicin encapsulated in polyethylene glycol-coated liposomes, and their pharmacokinetics (PK) is markedly different from that of doxorubicin.…”
Section: Discussionmentioning
confidence: 99%
“…Wilms tumor is the most frequent tumor of the kidney in infants and children. The incidence of Wilms tumor is 8.2 cases for every 1 million children younger than 15 years, or one case per 10,000 infants [1]. Approximately 650 cases of Wilms tumor are diagnosed in the United States each year.…”
Section: болалардаги буйрак ўсмалари ҳақида умумий маълумотлар (нефробластома)mentioning
confidence: 99%
“…The risk is lowest for KTS splice site mutations (1 of 27 cases, 4%). Bilateral Wilms tumor was more common in cases with WT1-truncating mutations (9 of 14 cases) than in cases with WT1 missense mutations (3 of 27 cases) [1,3].…”
Section: болалардаги буйрак ўсмалари ҳақида умумий маълумотлар (нефробластома)mentioning
confidence: 99%
See 1 more Smart Citation